Determination of the specific impulse of composite solid propellants under laser radiation; The 9th International Forum on Strategic Techology (IFOST-2014), September 21-23, 2014, Cox's Bazar, Bangladesh - Korotkikh A. G. Aleksandr Gennadievich; Yankovsky S. A. Stanislav Aleksandrovich; Arkhipov A.; Zarko V.; Kiskin A.; Glotov O. (Advanced Material & Nanotechnology, 2014)
Title screen